2012
DOI: 10.1128/ec.00190-12
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Inducible Nuclear Translocation of a Myb3 Transcription Factor in the Protozoan Parasite Trichomonas vaginalis

Abstract: cIn Trichomonas vaginalis, a novel nuclear localization signal spanning the folded R2R3 DNA-binding domain of a Myb2 protein was previously identified. To study whether a similar signal is used for nuclear translocation by other Myb proteins, nuclear translocation of Myb3 was examined in this report. When overexpressed, hemagglutinin-tagged Myb3 was localized to nuclei of transfected cells, with a cellular distribution similar to that of endogenous Myb3. Fusion to a bacterial tetracycline repressor, R2R3, of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…Oligonucleotides-Sequences of the oligonucleotides used in the present study are listed in Table 1 unless otherwise reported elsewhere (26,27).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Oligonucleotides-Sequences of the oligonucleotides used in the present study are listed in Table 1 unless otherwise reported elsewhere (26,27).…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid Construction-The HA-Myb3 expression plasmid, pAP65-2.1-ha-myb3, was obtained from a previous study (27). To produce a point mutation in HA-Myb3, a 5Ј-DNA fragment was amplified by polymerase chain reaction (PCR) from pAP65-2.1-ha-myb3 using a primer pair, tub90f and Myb3-(XnXЈ)-3Ј (where X indicates the amino acid to be mutated, n indicates the location of the residue, and XЈ is the mutated residue), and a 3Ј-DNA fragment was amplified by PCR using a primer pair, Myb3-(XnXЈ)-5Ј and SP6.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the three tvMybs, the tvMyb3 protein shows 83% aa sequence identity with human cMyb. Myb proteins are widely expressed in various avian and mammalian hosts and in plants [48][49][50][51]. The ciliates Sterkiella (also known as Oxytricha) and the ciliaphora Euplotes both carry myb genes in their genomes [52].…”
Section: Trichomonasmentioning
confidence: 99%